STRATEGI PENINGKATAN EFEKTIVITAS MONITORING DAN EVALUASI PENELITIAN KOTA MAGELANG - Krisno Wahyu Anggoro (Jendela Inovasi Daerah, 2021)
Research has been proven in developed countries that play an important role in regional development, so that in Indonesia is needed useful research. During the research in Indonesia, including in Magelang Municipality was carried out. This study aim to know the right strategi for the increasing the effect of monitoring and evaluation from the study program in Balitbang on Magelang Municipality. Population is are research conducted in the Magelang Municipality in 2017-2019 with a sample of research in Magelang Municipality in 2019. The process of analysis focused on strengths, opportunities, obtacles, and challenges faced in the process of monitoring and evaluating research and research effectiveness in Magelang Municipality. The results showed that the research conducted in Magelang Municipality still had obstacles, it is disobedience to the rules that had been applied in the evaluation monitoring process, so that commitment from relevant stakeholders was needed.